Training older workers and learners : - Monseley, James L. (John Wiley & Sons, Inc., 2007)
Training Older Workers and Learners is a groundbreaking resource that focuses exclusively on age 40-plus workers. This much-needed resource offers trainers expert guidance and practical tools designed to deliver effective training and re-training to older worker-learners (OWLS). Based on sound theory and best practices, the book shows how to maximize the workplace learning and performance potential of late-life learners.